Causes of residential mobility and Turkey practice - Özlü, Seda; Beyazli, Dilek (TeMA - Journal of Land Use, Mobility and Environment, 2020)
Residential mobility is an economic and social recovery process that determines urban growth and regional development. The urban population relocates due to the events in their lives or their dissatisfaction with the conditions. Such individual movements play a role in the construction of urban geography. The aim of the present study was to discuss the factors that affect the residential mobility in Ortahisar district in Trabzon, Turkey. To determine the mobility, a survey was conducted with 445 individuals in 11 neighborhoods with different socio-demographic, economic and physical attributes in Trabzon urban center. The survey findings were analyzed based on a) the analysis of the socio-demographic structure of households, b) evaluation of the residential buildings, c) the analysis of historical mobility, and d) the assessments of causality in mobility. In the study, the causal factors were analyzed based on the life cycle, life course and satisfaction approaches and mobility classification available in the literature, and the study findings were analyzed with descriptive statistics. It was determined that residential ownership, the structure of the household members, and proximity to the workplace factors were effective on residential mobility in Trabzon.